Xanthogranuloma of Choroid plexus: Case report and Review - D H Bhalodiya; J D Lakhani; S Shah; S Kumar; K J Pathak (Journal of Integrated Health Sciences)
Xanthogranuloma (XG), a condition of obscure pathogenesis and varied terminology, can occur in choroid plexus. We present here xanthogranuloma of the choroid plexus of lateral ventricle, who presented with headache, mild cognitive impairment and hemiplegia. It was difficult to determine whether bilateral small xanthogranuloma found on MRI was responsible for patient's presenting symptoms or not. Appraisal of clinical and pathological findings related to intracranial and intraventricular choroid plexus XG, is done from the available literature. Furthermore, review in topic of “relation of XG with arthrosclerosis” as well as “Dyslipidemia” is also done.